PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH DAN PENGAWASAN KEUANGAN DAERAH TERHADAP NILAI INFORMASI PELAPORAN KEUANGAN PEMERINTAH DAERAH (STUDI PEMERINTAH PROVINSI RIAU) - Nursewan, Kapian; -, Kennedy; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Based on the examination of the BPK in the second half of 2011 states that of 516 LKPD, BPK gives an unqualified opinion only 34 LKPD alone. An evaluation of 516 LKPD, there were 4,178 cases of weakness of the internal control system (SPI), which includes accounting control system weaknesses and reporting. It shows that the system of internal controls on government agencies have not been implemented optimally, so that it may have an influence on the value of information pelapran local government finance and examination is due to local government financial statements do not meet the values characteristic of information from the financial statements themselves. Writer wanted to know the influence of these factors on the value of the local government financial reporting information. To test the hypothesis, the author uses primary data. Technical analysis of the data using a system of internal control and financial oversight of local government as an independent variable and the value of local government financial reporting information as the dependent variable. Once the data was analyzed, it was found that all the above factors significantly influence the value of government financial reporting information. That is, if the system of internal control and financial oversight of local government, the better the information value of the resulting financial reporting will better the government.Keywords: value of information, internal control, government, financial, and supervision.